An Introduction to the Underground Economy of Romania - Loredana Maftei (CES Working Papers, 2014)
Shadow economy affected for a long time Romania, even since the old regime. During the period 1995-1996, the expansion of this phenomenon has become more serious. Along with Bulgaria, Romania is the second most affected country in the Eastern part of Europe, the shadow economy reaching around 28% of national GDP. This process is boosted by a high level of tax evasion, black labor and overregulation. With the ascension into EU, Romania made considerable efforts to combat the underground economy through a increase of electronic payments, credit card and deposit use.
Keywords: O17; O5; E26; 330; shadow economy; overregulation; black labor; tax evasion